Simulation on Connecting Climate Market Systems - World Bank Group (World Bank, Washington, DC, 2019)
The Paris Agreement introduced a bottom-up approach for addressing climate change by enabling countries to pledge individual commitments through nationally determined contributions (NDCs). Furthermore, Article 6 of the Paris Agreement recognizes that Parties may engage in bilateral cooperative approaches, including through the use of internationally transferred mitigation outcomes (ITMOs), to achieve their NDCs. Heterogeneous climate markets may have different governance systems and technological approaches. Information about mitigation outcomes (MOs) or emission reductions is currently collected in a variety of repositories, including spreadsheets and registries, with different levels of information. The differences in these processes may constrain market integration and add to the complexity of tracking and recording transactions. Against this backdrop, there is a need to create a new architecture to support transparency and enhance the tradability of climate assets across jurisdictions while ensuring the integrity of trades. The Kyoto Protocol utilized an International Transaction Log (ITL), operated by the United Nations Framework Convention on Climate Change (UNFCCC), to facilitate communication between registries and maintain a transaction log to ensure accurate accounting and verification of transactions proposed by connected registries. However, under the Paris Agreement, which may rely on a decentralized approach to markets under Article 6.2, climate negotiators are still determining whether a centralized infrastructure should continue, the functions it could perform, and to which market mechanisms or transactions it would apply. Consistent with the bottom-up ethos of the Paris Agreement, there is value in demonstrating an approach to link registry systems in a peer-to-peer arrangement.